Chopper stabilized, low-power, low-noise, front end interface circuit for capacitive CMOS MEMS sensor applications - Sutri, N.Y. (2013)
In this paper, a chopper stabilized fully differential CMOS pre-amplifier circuit is presented. The proposed circuit is designed for sub-atto Farad capacitive CMOS MEMS sensing applications. Chopper stabilization technique is employed to minimize flicker (1/f) noise and offsets in the circuit. The proposed circuit is designed using MIMOS 0.35 Î¼m AMS CMOS 3.3 V technology and simulation results from Cadence Virtuoso Spectre circuit simulator show that the proposed circuit is able to detect capacitance changes ranging from 0.0375 aF to 37.5 fF, attain an input inferred noise of 0.9 nV/âvHz, gain of 18.1 dB at 3-dB frequency of 5.5 MHz with total power consumption of 0.33 mW. Â© by the author(s).